Rachel Seelig. Strangers in Berlin: Modern Jewish Literature Between East and West, 1913-1933. Ann Arbor: U of Michigan P, 2016. - Adam J Sacks (Studies in 20th & 21st Century Literature, 2018)
Review of Rachel Seelig. Strangers in Berlin: Modern Jewish Literature Between East and West, 1913-1933. Ann Arbor: U of Michigan P, 2016. 225 pp.
Keywords: Berlin; Modernism; Poetry; Jews